Macroeconomic Performance Under Alternative Exchange Rate Regimes : Does Wage Indexation Matter? - Jadresic, Esteban (IMF Working Papers; Working Paper, 1998)
This paper reexamines the macroeconomic effects of wage indexation in an open economy under alternative exchange rate regimes. The main finding is that, once the lags in actual indexation rules are considered, wage indexation affects output behavior substantially less than posited in the previous academic literature. This result implies that the academic view that wage indexation makes a flexible exchange rate generally preferable is unwarranted and suggests that the choice of exchange rate regime with and without wage indexation depends on similar factors. The analysis also reveals that the net effects of wage indexation on macroeconomic stability are ambiguous.